Morphology and growth pattern of Nike fish (amphidromous goby larvae) in Gorontalo Waters, Indonesia - Nuralim Pasisingi; Abdul Hafidz Olii; Sitty Ainsyah Habibie (Tomini Journal of Aquatic Science, 2020)
Nike is a terminology used by Gorontalo local community to name schooling of minuscule amphidromous goby fish that has a limited appearance in Gorontalo waters. Understanding the biological performance of Nike fish is vital for implementing management and conservation strategy. This study aims to analyze daily recruitment and to determine growth patterns of Nike fish population in nature. Sampling was conducted in the Gorontalo waters during March, April, and May 2018 using a fish net with a mesh size of 0.5 inches. The duration of the appearance of Nike schooling in waters varies every month. The number of fish samples collected each month in this study ranged from 150 to 300 individuals. This study reveals that body color diversity and morphology of Nike fish strongly alleged to depend on where and how long they appear in the waters. Based on the daily recruitment pattern, Nike fish population distributed in Gorontalo waters is predicted to consist of individuals from multi-generation with an average length range of 1.848–2.805 cm. During the sampling time, a positive allometric growth pattern indicated by the population.